Penyuluhan Penggunaan Obat Rasional (POR) dalam Swamedikasi pada Masyarakat di Desa Sejahtera Kecamatan Palolo Kabupaten Sigi - niluh, Niluh Puspita Dewi; Marselinus, Marselinus; Dipayana, I Made (LPPM Universitas Duta Bangsa Surakarta, 2022)
Self-medication is a common activity carried out by a person when he is sick. Proper self-medication by providing information provided by health workers will help the patient's healing process by optimizing therapy. Irrational management can result in various disadvantages such as medication errors due to inaccurate self-diagnosis; drug use is not appropriate because of the acquisition of incorrect information from the media; waste of time and costs; can cause unwanted drug reactions such as sensitivity, allergies, side effects or resistance. The use of drugs is said to be rational, if the patient receives the right drug for clinical needs, in doses that meet the needs for a sufficient period of time, and at affordable costs for both individuals and society. This activity was carried out with the aim to increase the understanding and knowledge of the community in Sejahtera Village, Palolo District, Sigi Regency, especially about rational medicine and the provision social assistance. Counseling is given by interactive lecture method through posters and distribution of leaflets. The effectiveness of the extension was tested by giving a partner satisfaction questionnaire to the activities carried out. The results of the activity observations showed that the Partners were satisfied with the outreach activities carried out.